Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2016)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2015, N applied alone increased yields 70 bu/a, whereas P applied alone increased yields only 12 bu/a. Nitrogen and P applied together increased yields up to 129 bu/a. This is below the 10 year average, where N and P fertilization increased corn yields up to 144 bu/a. Application of 120 lb/a N (with P) produced about 98% of maximum yield in 2015, which is 5% more than the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields only 1 bu/a. Average grain N content reached a maximum of 0.6 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu).
Keywords: Nitrogen fertilization; phosphorus fertilization; irrigated corn; long-term fertility; nutrient removal